Kontribusi Riverside Forest Sebagai Aliran Punk Football Terhadap Industri Sepak Bola Di Kota Bandung Pada Tahun 2021-2023 - Haekal Bachtiar (Jurnal Sosial Humaniora, 2025)
Punk Football is a subcultural phenomenon born from the meeting of two cultural elements: the rebellious spirit of punk and the passion for soccer. Riverside Forest is an alternative club to the chaos of Indonesian football. The majority of the club's funding is collectively funded by its supporters. The purpose of this research is to be able to describe the history and contribution of Riverside Forest to the soccer industry in Bandung City in 2021-2023. The method used is the historical research method which has four stages, namely heuristics, criticism, interpretation, and historiography. The club's philosophy is inseparable from criticism of the commercialization of modern football and their focus on building inclusive and community-based football with its supporters. Bird Dead Brigade (BDB) and Riverside Forest itself have a crucial role in shaping local identity and making a real contribution to the football industry. As key elements in the soccer ecosystem, they are not only fans, but also social actors that connect the sport to the cultural values, history, and pride of Bandung. Both Bird Dead Brigade (BDB) and Riverside Forest FC contribute significantly to the soccer industry, especially in Bandung. Their presence at the stadium drives ticket, merchandise and sponsorship revenue.